2017
DOI: 10.1021/acs.orglett.7b00375
|View full text |Cite
|
Sign up to set email alerts
|

Halogen-Bond-Promoted Photoactivation of Perfluoroalkyl Iodides: A Photochemical Protocol for Perfluoroalkylation Reactions

Abstract: A new protocol for photochemical perfluoroalkylation reactions using perfluoroalkyl iodide, amine additive, and THF solvent is reported. This protocol does not require a photoredox catalyst and proceeds at ambient temperature with irradiation from a compact fluorescent lamp, low-intensity UV lamp, or sunlight. This protocol can be applied to the synthesis of perfluoroalkyl-substituted phenanthridines as well as effect the iodo-perfluoroalkylation of alkenes/alkynes and the C-H perfluoroalkylation of electron-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
135
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(140 citation statements)
references
References 60 publications
4
135
0
1
Order By: Relevance
“…Another visible‐light‐induced modification of tryptophan was reported by Chen and co‐workers . In this case, the authors observed that perfluoroalkyl iodides could be activated in the presence of tertiary amines (i.e., N , N , N ′, N ′‐tetraethylethylenediamine (TEEDA)) or with THF as a solvent to form complexes that absorbed in the near‐UV range.…”
Section: Photocatalytic Modification Of a Residue At The Single Aminomentioning
confidence: 87%
“…Another visible‐light‐induced modification of tryptophan was reported by Chen and co‐workers . In this case, the authors observed that perfluoroalkyl iodides could be activated in the presence of tertiary amines (i.e., N , N , N ′, N ′‐tetraethylethylenediamine (TEEDA)) or with THF as a solvent to form complexes that absorbed in the near‐UV range.…”
Section: Photocatalytic Modification Of a Residue At The Single Aminomentioning
confidence: 87%
“…Interestingly, this reaction worked well by using a solar simulator (Table , entry 8), suggesting that our methodology could effectively be conducted under direct sunlight irradiation. Recently, the group of Chen demonstrated that simple primary alkyl amines (such as EDA) can be used as additives (1.5–3.0 equiv), in tetrahydrofuran, to promote the photoactivation of perfluoroalkyl iodides through halogen bond formation . In the light of this, the amine functionalities on the NCNDs could also, in principle, give halogen‐bonded adducts with 1 a under the reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, we have chosen n ‐butylamine ( n Bu‐NH 2 ) as model compound to mimic the chemical behavior of the primary amino groups situated at the surfaces of the nanoparticles. A series of 19 F NMR spectroscopic studies (see pages S10 and S11 in the Supporting Information), in deuterated DMF, demonstrated that n Bu‐NH 2 may behave as acceptor in the formation of halogen‐bonded derivatives with 1 a (binding constant, K =2.13 m −1 ) . Therefore, the amine‐rich NCNDs used are likely engaged in halogen‐bonding interaction with 1 a .…”
Section: Resultsmentioning
confidence: 99%
“…Recent decades has witnessed the blooming of photochemical irradiation as a powerful approach for challenging transformations. [3] Thus, the development of effective photocatalyst-free transformations with substrates that were not capable of forming EDA complex is a challenging goal in organic synthesis but yet remains largely unexplored. On the other hand, there are relatively fewer examples of an organic transformation driven by visible-light without a photocatalyst.…”
mentioning
confidence: 99%
“…Atom transfer radical addition (ATRA) of haloalkanes to alkenes and alkynes serves as an atom-economical method of simultaneously forming CÀC and CÀX bonds, and it has been recognized as a useful tool in organic chemistry. [1][2][3] Besides, these methods constantly employed harsh conditions and lack broad functional group tolerance. By using light irradiation, the radical process could be initiated via a direct energy transfer, [5n-p] otherwise, a photocatalyst was always required to activate the reactants which were not able to absorb the visible light (Scheme 1, Equation (a)).…”
mentioning
confidence: 99%